2014
DOI: 10.2340/00015555-1797
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Spectrum of Lichen Sclerosus in Male Patients – A Retrospective Study

Abstract: Lichen sclerosus (LS) is a chronic dermatosis mainly localised to the anogenital area. The aim of this study was to investigate the clinical features of LS in adult men. A retrospective analysis of records from 771 patients diagnosed with LS was made and a questionnaire was sent to all patients. The results showed that the clinical spectrum was wide. Itch, tenderness and pain were frequently reported and more than half of the patients reported that LS had a negative impact on their sexual health. Phimosis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 27 publications
3
28
1
2
Order By: Relevance
“…Several risk factors for penile cancer have been identified, including human papillomavirus (HPV) infection, phimosis and poor hygiene, smoking, chronic inflammation and socioeconomic status . Male circumcision, especially in the neonatal/infant period, has been found to have a protective role in penile cancer, as well as penile inflammation .…”
Section: Introductionmentioning
confidence: 99%
“…Several risk factors for penile cancer have been identified, including human papillomavirus (HPV) infection, phimosis and poor hygiene, smoking, chronic inflammation and socioeconomic status . Male circumcision, especially in the neonatal/infant period, has been found to have a protective role in penile cancer, as well as penile inflammation .…”
Section: Introductionmentioning
confidence: 99%
“…[31] Penile cancer was seen in 1% of 771 Swedish men aged 48.6 years (range 22–92) diagnosed with LS during 1997–2007. [71] Another study found penile cancer in 4%–8% of men with LS. [104]…”
Section: Resultsmentioning
confidence: 99%
“…[109] In a Swedish study, 30% of men reported that outcome of local steroid treatment was “good,” while 37% said it was “medium” and 16% “poor” (17% failed to answer). [71] An Indian study of men aged 20–45 years with LS reported a preference by all for circumcision rather than use of steroid creams. [111] In another Indian study, 77% received circumcision for treatment.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is different from the study done by Kantere et al where prepuce along with glans was the most common site of involvement. 5 The close resemblance of LS to vitiligo also warrants proper differentiation both clinically and histopathologically. There were two cases of Balanitis xerotica obliterans (BXO), both presented clinically as thickened, contracted fissured prepuce fixed over the glans leading to phimosis.…”
Section: Discussionmentioning
confidence: 99%